2021
DOI: 10.14202/vetworld.2021.1202-1209
|View full text |Cite
|
Sign up to set email alerts
|

Preferred and undesirable genotypes of bGH and bIGF-1 genes for the milk yield and quality of black-and-white breed

Abstract: Background and Aim: The market demand for the quality of milk and dairy products, in particular in terms of such indicators as fat content, the amount and composition of milk protein, etc., is growing. Thus, the need for the selection of dairy herds using genetic markers associated with qualitative traits of milk productivity is becoming urgent. This study aimed to determine the preferred and undesirable genotypes of the AluI polymorphism of the growth hormone gene and SnaBI polymorphism of the insulin-like gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…(Zhou et al, 2006;Maylinda, 2011;Moravcikova et al, 2012;Hazuchova et al, 2013). Studies conducted on different cattle types and buffaloes have reported that GH-AluI gene polymorphisms affect meat yield, pre-slaughter body weight, carcass meat weight, slaughter weight and growth data (Pereira et al, 2005;Curi et al, 2006;Sedykh et al, 2020;El-Komy et al, 2021) Parallel to our research, polymorphic association studies analyzing somatotropic axis genes together have generally associated these genes with growth and reproduction data but not with milk yield, especially GH/AluI and IGFI/SnaBI (Balogh et al, 2008;Ulyanov et al, 2021). The two different META analysis studies show that the common L allele was dominant and no significant difference was found in the results of the meta-analysis and subgroup analysis for the milk yields in the LL, LV, and VV genotypes Akcay et al, 2020;Bangar et al, 2021).…”
Section: Discussionsupporting
confidence: 61%
“…(Zhou et al, 2006;Maylinda, 2011;Moravcikova et al, 2012;Hazuchova et al, 2013). Studies conducted on different cattle types and buffaloes have reported that GH-AluI gene polymorphisms affect meat yield, pre-slaughter body weight, carcass meat weight, slaughter weight and growth data (Pereira et al, 2005;Curi et al, 2006;Sedykh et al, 2020;El-Komy et al, 2021) Parallel to our research, polymorphic association studies analyzing somatotropic axis genes together have generally associated these genes with growth and reproduction data but not with milk yield, especially GH/AluI and IGFI/SnaBI (Balogh et al, 2008;Ulyanov et al, 2021). The two different META analysis studies show that the common L allele was dominant and no significant difference was found in the results of the meta-analysis and subgroup analysis for the milk yields in the LL, LV, and VV genotypes Akcay et al, 2020;Bangar et al, 2021).…”
Section: Discussionsupporting
confidence: 61%
“…The nucleotide sequence polymorphism of the insulinlike growth factor-1 gene bIGF-1 in the P1 promoter region was identified by Hines H.C. (Ulyanov et al, 2021). Amplified PCR products of the bovine bIGF-1 gene (249 bp) were digested using the restriction enzyme SnaBI.…”
Section: Methodsmentioning
confidence: 99%
“…One of the main sectors of the Kazakh economy is animal husbandry, in which dairy farming plays an important role [ 11 ]. In Kazakh farms, between 20% and 40% of cows are infected with mastitis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%